(untitled) (International Journal of Engineering and Computer Science, 2015)
This paper presents a two stage operational transconductance amplifier realized using floating gate MOSFETs in differential inputs. A configuration of two stage operational transconductance amplifier using floating gate MOSFET for low power and low voltage applications is presented. Here we design a two stage operational transconductance amplifier using floating gate MOSFET in HSPICE 180nm CMOS technology with the entire transistor in the saturation region. The simulated output transient response and frequency response is shown for a supply voltage of 1V using Cosmos Scope in HSPICE. DC gain is 60dB, settling time 550ns and power consumption 3.06pW.